Pharmacokinetics and Bioequivalence Study of Clindamycin Hydrochloride Formulations after Single-dose Administration in Healthy Chinese Male Volunteers - Li, Jing; Wang, Na; Zhang, Zun-Jian; Tian, Yuan; Tang, Weiguo; Chen, Yun (Arzneimittelforschung, 2008)
The aim of the present study was to compare the bioavailability of clindamycin (CAS 18323-44-9) from three clindamycin hydrochloride (CAS 21 462-39-5) capsules (clindamycin 75 mg capsule as test 1 preparation, 150 mg capsule as test 2 preparation and a commercially available original 150 mg capsule of the drug as reference preparation) in 24 Chinese healthy male volunteers, aged between 22 and 28. The study was conducted according to a randomized, double-blind, 3-period, 3-treatment, 3-sequence, single-dose, crossover design with a wash-out phase of 7 days. Blood samples for pharmacokinetic profiling were taken up to 14 h post-dose, and clindamycin plasma concentrations were determined with a validated liquid chromatography-electrospray ionization-mass spectrometry (LC-ESI-MS) method. Maximum plasma concentrations (Cmax) of 3.06 ± 1.10 µg/mL (test 1), 3.10 ± 1.59 µg/mL (test 2) and 3.06 ± 1.15 µg/mL (reference) were achieved. Areas under the plasma concentration-time curve (AUC0–∞) of 10.73 ± 4.29 µg · h/mL (test 1), 10.54 ± 4.10 µg · h/mL (test 2) and 11.29 ± 4.98 µg · h/mL (reference), AUC0–t of 10.32 ± 4.09 µg · h/mL, 10.26 ± 3.96 µg · h/mL, 10.94 ±4.86 µg · h/mL were calculated. The median Tmax was 0.80 ± 0.52 h, 0.77 ± 0.37 h, 1.01 ± 0.6 h for test 1, test 2 and reference formulation, respectively. Plasma elimination half-lives (t1/2) of 2.72 ± 0.58 h (test 1), 2.39 ± 0.37 h (test 2) and 2.63 ± 0.66 h (reference) were determined. Both primary target parameters, AUC0–∞ and AUC0–t were tested parametrically by analysis of variance (ANOVA) and relative bioavailabilities were 98.0 ± 16.2% (test 1) and 97.2 ± 20.3% (test 2) for AUC0–∞, 97.5 ± 16.3% (test 1) and 97.8 ± 20.2% (test 2) for AUC0–∞. Bioequivalence between test and reference preparation was demonstrated for both parameters, AUC0–∞ and AUC0–t. The 90% confidence intervals of the T/R-ratios of logarithmically transformed data were in the generally accepted range of 80%–l25%. That means that the two test formulations are bioequivalent to the reference formulation for clindamycin.
Keywords: Antibiotics; CAS 18323-44-9; CAS 21462-39-5; Clindamycin; Clindamycin hydrochloride, bioequivalence, pharmacokinetics